Legal Certainty of Contract for Difference Derivative Transactions in the Alternative Trading System in Indonesia - Firmansyah, Teguh; Rahayu, Sang Ayu Putu (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Interest in investment in Indonesia has experienced a significant increase in recent years. This trend is driven by technological advancements that facilitate access to various investment platforms, such as digital-based applications and investment e-commerce. However, not all individuals possess adequate understanding of investment risks and potential, which may lead to suboptimal decision-making.Purposes of the Research: The study aims to analyze the multilayered regulatory structure established to ensure market stability, investor protection, and alignment with national economic objectives, as well as to identify the role of key regulatory institutions within the derivative market ecosystem, particularly in relation to Contract for Difference (CFD).Methods of the Research: The study utilizes a normative legal analysis methodology, examining primary legal sources, including laws, government regulations, and directives from regulatory institutions.Results Main Findings of the Research: Indonesia's derivatives trading is governed by a multi-layered regulatory framework to ensure market transparency, security, and stability. The primary legal basis is Law No. 32 of 1997 on Commodity Futures Trading, amended by Law Number 10 of 2011, which establishes BAPPEBTI as the main regulator. Government Regulation Number 9 of 1999 sets operational guidelines, while BAPPEBTI Regulation No. 109/Bappebti/PER/01/2014 and No. 5 of 2017 regulate alternative trading systems, including CFD.